BIOLOGICAL ACTIVITY OF ß-GLUCANS FROM EDIBLE MUSHROOM, SCHIZOPHYLLUM COMMUNE IN THAILAND - N. A. PHUKET, SAMRAJ RATTANADILOK; SANGKAEW, TITIMA; CHANAPAN, PIYATIDA; TECHAOEI, SURACHAI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to determine the antioxidant of ß-glucans from an edible mushroom, Schizophyllum commune in Thailand. Methods: The antioxidant activity of ß-glucans was measured in terms of hydrogen donating or radical scavenging ability by 2, 2-diphenyl-1- picrylhydrazyl (DPPH) method,2,2´-azinobis-(3-ethyl-benzothiazoline-6-sulfonic acid (ABTS) radical scavenging activity analysis, and total phenolic compounds. The ß-glucans structure was analyzed using Fourier-transform infrared spectrophotometer. Results: The ß-glucans were extracted from S. commune and tested biological activities. Using the Folin–Ciocalteu Reactive method, we found that the phenolic compound contents of ethanol extracts of the mushroom sample were 284.41±1.22 mgGAE/g extract. The IC50 radical scavenging ability (DPPH) and IC50 radical scavenging activity (ABTS) of ß-glucans were 0.829±0.006 and 0.724±0.021 mg/mL, respectively. Conclusion: The ß-glucans from S. commune in Thailand showed a potent antioxidant activity and it will be able to apply in pharmaceutical cosmetics.